The matriarch : Barbara Bush and the making of an American dynasty - Page, Susan (New York, NY : Twelve, Hachette Book Group., 2019)
This biography is informed by more than one hundred interviews with Bush friends and family members, hours of conversation with Mrs. Bush herself in the final six months of her life, and access to her diaries that spanned decades; examining not only her public persona but also less well-known aspects of her remarkable life. As first the wife and then the mother of American presidents, she made history as the only woman to see -- and advise -- both her husband and son in the Oval Office. As with many women of her era, Barbara Bush was routinely underestimated, her contributions often neither recognized nor acknowledged, but she became an astute and trusted political campaign strategist, invested herself deeply in expanding literacy programs in America, played a critical role in the end of the Cold War, and led the way in demonstrating love and compassion to those with HIV/AIDS Provided by the publisher.
Keywords: Bush, Barbara, 1925-2018 -- Biography; Bush, George W. 1946- Family -- Biography